Childhood Cognition and Age-Related Change in Standing Balance Performance From Mid to Later Life: Findings From a British Birth Cohort - Blodgett, Joanna M (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Cognitive processing plays a crucial role in the integration of sensory input and motor output that facilitates balance. However, whether balance ability in adulthood is influenced by cognitive pathways established in childhood is unclear, especially as no study has examined if these relationships change with age. We aimed to investigate associations between childhood cognition and age-related change in standing balance between mid and later life. METHODS: Data on 2,380 participants from the MRC National Survey of Health and Development were included in analyses. Repeated measures multilevel models estimated the association between childhood cognition, assessed at age 15, and log-transformed balance time, assessed at ages 53, 60–64, and 69 using the one-legged stand with eyes closed. Adjustments were made for sex, death, attrition, anthropometric measures, health conditions, health behaviors, education, other indicators of socioeconomic position (SEP), and adult verbal memory. RESULTS: In a sex-adjusted model, 1 standard deviation increase in childhood cognition was associated with a 13% (95% confidence interval: 10, 16; p < .001) increase in balance time at age 53, and this association got smaller with age (cognition × age interaction: p < .001). Adjustments for education, adult verbal memory, and SEP largely explained these associations. CONCLUSIONS: Higher childhood cognition was associated with better balance performance in midlife, with diminishing associations with increasing age. The impact of adjustment for education, cognition and other indicators of SEP suggested a common pathway through which cognition is associated with balance across life. Further research is needed to understand underlying mechanisms, which may have important implications for falls risk and maintenance of physical capability.